Review of PPIUCD at tertiary care centre in Southern Rajasthan - Sharma, Nirmala; Gupta, Vinita; Sharma, Ashutosh (Asian Journal of Medical Sciences, 2021)
Background: This study was conducted to observe the acceptance rate and safety for PPIUCD as PPIUCD was used as contraceptive method under family welfare program in this institute. Aims and Objectives: To see pattern of acceptance and safety of PPIUCD among women admitted for childbirth. Materials and Methods: A prospective, preformed semi-structured questionnaire-based observational study was conducted between September 2012 and August 2020 in the Government Medical College Kota. CuT380A was used as PPIUCD for insertion. WHO medical eligibility criteria were met along with inclusion and exclusion criteria. After counseling and consent, PPIUCD was inserted post-placentaly and during LSCS. Acceptance rate was calculated along with safety profile. Results: In the present study majority of patients were in the age group of 21–30 years. 44.26% women were second para. 96.35% insertions were uneventful during the study. The most common reason for acceptance and refusal of PPIUCD was reversibility and for refusal was fear of complications, respectively. The acceptance was increasing over the years. On follow-up majority of clients had no complaints. Among those who had complaints, irregular bleeding was most common. Major cause of requesting for removal was irregular bleeding. Continuation rate was found to be 91.91% and 85.30% at 6 weeks and 6 months, respectively. Conclusion: PPIUCD is a safe and effective method of contraception. Acceptance rate is increasing over the years and which can further increase with antenatal, intra natal and postnatal counseling along with counseling of husband/family attendants and management of side effects.